Sedentary time across the transition to retirement and after an activity tracker intervention - Suorsa, Kristin (fi=Turun yliopisto|en=University of Turku|, 2021)
This study aimed to examine how accelerometer-measured daily total and prolonged sedentary time change across the transition to retirement using annual measurement data from the Finnish Retirement and Aging (FIREA) study (n=689). Another aim was to examine the effect of a 12-month activity tracker-based intervention on sedentary time among recent retirees using data from the REACT trial (n=231). The final aim was to compare sedentary time estimates of the wrist-worn accelerometers used in both studies to the estimates obtained by a more reliable method, a thighworn accelerometer. Daily total sedentary time only changed among women retiring from manual occupations. Their daily total sedentary time increased by 54 minutes immediately after the transition to retirement. Prolonged sedentary time increased by half an hour across gender and occupational groups. The timing of the changes in relation to retirement differed between genders, as women’s prolonged sedentary time increased immediately after the transition to retirement, whereas the increase in men’s prolonged sedentary time was more gradual from the last years at work to a few years after retirement. The activity tracker-based intervention targeted at the first years after retirement did not elicit changes in daily total or prolonged sedentary time over 12 months in comparison to the controls. The wrist-worn accelerometer either underestimated or overestimated daily total sedentary time in comparison to the thigh-worn accelerometer, depending on the method used. However, withinindividual differences in sedentary time were similarly captured by each method, suggesting that the observed changes in sedentary time across retirement and the intervention were reliable. This study indicates that interventions to reduce sedentary time may be the most effective when targeted at the first years after retirement among women, but that the benefit for men may be highest during the last years in work life. As an activity tracker alone was insufficient to reduce sedentary time in the long term, other approaches or additional intervention components may be needed to attain long-term changes in sedentary time

Paikallaanolo eläkkeelle siirryttäessä ja aktiivisuusintervention jälkeen Tämän tutkimuksen tavoitteena oli selvittää, miten liikemittarilla mitattu päivän paikallaanoloaika ja pitkittynyt paikallaanolo muuttuvat eläköidyttäessä käyttäen Finnish Retirement and Aging (FIREA)-tutkimuksen vuosittain toistettuja mittauksia (n=689). Tavoitteena oli myös tutkia, onko aktiivisuusrannekkeella vaikutusta paikallaanoloon juuri eläköityneillä henkilöillä käyttäen koe- ja kontrolliasetelmaa REACT-interventiotutkimuksen aineistossa (n=231). Tutkimuksessa mitattiin paikallaanoloa ranteessa pidettävällä liikemittarilla, minkä vuoksi tavoitteena oli myös vertailla rannemittarilla saatuja paikallaanolon estimaatteja reisimittarilla saatuihin luotettavampiin paikallaanolon estimaatteihin. Päivän kokonaispaikallaanolo muuttui ainoastaan naisilla, jotka eläköityivät fyysisistä ja palveluammateista. He lisäsivät paikallaanoloaikaansa 54 minuutilla päivässä heti eläköitymisen jälkeen. Pitkittynyt paikallaanolo lisääntyi sen sijaan noin puolella tunnilla päivässä sekä naisilla että miehillä ammatista riippumatta. Muutosten ajoittuminen eläköitymiseen nähden erosi naisten ja miesten välillä, koska naisilla pitkittyneen paikallaanoloajan lisääntyminen tapahtui heti eläköitymisen jälkeen, kun taas miehet lisäsivät pitkittynyttä paikallaanoloa tasaisesti viimeisistä työvuosista ensimmäisiin eläkevuosiin. Eläköitymisen jälkeiselle ajalle kohdistettu vuoden kestoinen aktiivisuusrannekeinterventio ei saanut aikaan muutoksia kokonaispaikallaanoloajassa eikä pitkittyneessä paikallaanoloajassa kontrolliryhmään nähden. Verrattuna reisimittariin, rannemittarilla saadut tulokset joko aliarvioivat tai yliarvioivat paikallaanoloa kiihtyvyysmittaridatan prosessointimenetelmästä riippuen. Havaitut paikallaanoloajan muutokset olivat kuitenkin samanlaisia menetelmästä riippumatta, joten paikallaanolon muutoksia koskevat tulokset ovat todennäköisesti luotettavia. Tämän tutkimuksen tulokset osoittavat, että interventiot paikallaanolon vähentämiseksi ovat perusteltuja pian eläköitymisen jälkeen naisilla, kun taas miehillä suurimmat hyödyt voidaan mahdollisesti saavuttaa jo viimeisinä työvuosina. Aktiivisuusrannekkeen käyttö ei riittänyt vähentämään paikallaanoloa pitkällä aikavälillä, minkä vuoksi rannekkeen lisäksi voidaan tarvita muita keinoja.